Clinical and laboratory characteristics of chronic spontaneous urticaria with connective tissue diseases: A cross-sectional study - Songül Çildağ,; Gökhan Sargın,; Taşkın Şentürk, (Archives of Rheumatology, 2022)
Objectives: The aim of this study was to investigate the frequency of connective tissue diseases (CTDs) in patients with chronic spontaneous urticaria (CSU) and to evaluate clinical and laboratory characteristics of CSU accompanied by CTDs. Patients and methods: Between January 2017 and December 2020, a total of 390 CSU patients (120 males, 270 females; mean age: 38.9±13.7 years; range, 18 to 78 years) were included in the study. Clinical and laboratory characteristics of CSU in patients with and without CTD were analyzed. Results: A total of 6.4% patients (n=25) with CSU had CTD, and the rate was found to be 8.9% in female patients (n=24). In these patients, Sjögren syndrome (SS) was seen in 15 (5.5%), rheumatoid arthritis in five (1.85%), undifferentiated connective tissue disease in three (1.11%), and systemic lupus erythematosus in one (0.37%). Anti-thyroglobulin antibody, rheumatoid factor, anti-cyclic citrullinated peptide antibody, antinuclear antibody positivity, low complement 4 level, and erythrocyte sedimentation rate were significantly different between CSU patients with and without CTD (p=0.013, p<0.001, p<0.001, p<0.001, p=0.0182, p<0.001, respectively). Conclusion: Our study results suggest that CSU is associated with CTDs, particularly with Sjögren syndrome. Every patient diagnosed with CSU should be questioned about rheumatic symptoms, particularly female patients and those having later-onset CSU.